A scoping review to identify and map the multidimensional domains of pain in adults with advanced liver disease - Franklin F. Gorospe; Laura Istanboulian; Martine Puts; David Wong; Elizabeth Lee; Craig M. Dale (Taylor & Francis Group, 2020)
Background: Pain is a significant problem in adults living with advanced liver disease, having limited guidance available for its clinical management. While pain is considered a multidimensional experience, there have been limited reviews of the pain literature in advanced liver disease conducted with a multidimensional framework. Aims: The goal of this scoping review was to identify and map the multidimensional domains of pain in adults with advanced liver disease using the biopsychosocial model. Methods: We used Arksey and O'Malley's scoping framework. A search was conducted in MEDLINE, Embase, AMED, and CINAHL databases and the gray literature using specific eligibility criteria (1990-2019). Citation selection and data extraction were performed by two independent reviewers and in duplicate. Results: Of the 43 studies that met inclusion criteria, 51% were from North America and 93% utilized quantitative methods. The combined studies reported on 168,110 participants with ages ranging between 23 to 87 years. Only 9% reported an objective scoring system for liver disease severity. Few studies reported pain classification (9%) and intensity (16%). Pain prevalence ranged between 18% and 100%, with pain locations including joint, abdomen, back, head/neck, and upper/lower extremities. We identified and mapped 115 pain factors to the biopsychosocial model: physical (81%), psychological (65%), and sociocultural (5%). Only 9% measured pain using validated multidimensional tools. Pharmacological intervention (92%) prevailed among pain treatments. Conclusions: Pain is not well understood in patients with advanced liver disease, having limited multidimensional pain assessment and treatment approaches. There is a need to systematically examine the multidimensional nature of pain in this population.